An Open-Label, 52-Week, Phase III Trial of Duloxetine in Japanese Patients with Chronic Low Back Pain. Issue 8 (11th March 2019) - Konno, Shin-ichi; Alev, Levent; Oda, Natsuko; Ochiai, Toshimitsu; Enomoto, Hiroyuki
Abstract: Objective: To evaluate the safety and efficacy of duloxetine treatment for 52 weeks. Design: Multicenter, open-label, phase III clinical study. Setting: Forty-one medical institutions in Japan. Subjects: Japanese patients with chronic low back pain (CLBP). Methods: Duloxetine 60 mg once-daily was administered for 52 weeks. Safety was evaluated based on adverse events (AEs), vital signs, laboratory test values, electrocardiogram, Columbia-Suicide Severity Rating Scale, and occurrence of falls. The efficacy outcome measures were the Brief Pain Inventory (BPI; average pain, worst pain, least pain, and pain right now), BPI Interference, Patient's Global Impression of Improvement (PGI-I), Clinical Global Impressions of Severity (CGI-S), Roland-Morris Disability Questionnaire–24 (RDQ-24), 36-Item Short-Form Health Survey (SF-36), and European Quality of Life-5 Dimensions Questionnaire (EQ-5D). Results: In total, 151 patients (83 who completed a 14-week placebo-controlled superiority trial and 68 newly registered patients) were enrolled. The incidence rates of AEs and adverse drug reactions (ADRs) were 86.1% and 50.3%, respectively. ADRs with an incidence of ≥5% were somnolence, constipation, nausea, and dry mouth. Treatment discontinuation for AEs occurred in 16 patients. A significant reduction in the BPI average pain score (mean ± SD) was observed at all assessment time points from week 2 (−1.02 ± 1.37) to week 50 (−2.26 ± 1.63), compared with baseline. BPI pain severity (worst pain, least pain, and pain right now), BPI Interference, PGI-I, CGI-S, RDQ-24, SF-36, and EQ-5D showed significant improvement. Conclusion: Japanese patients with CLBP had significant pain reduction over 52 weeks without new safety concerns.